2017
DOI: 10.3991/ijet.v12i01.6483
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Learning Mode of a Multimedia-based "English Literature" Learning System

Abstract: Abstract-In this paper, a multimedia-based English pronunciation learning system was designed. On this basis, a self-adaptive learning mode which consists of the teaching mode and the independent learning mode was proposed. The self-adaptive teaching model uses corpus technology and covers the exploratory "3I" (Illustration-Interaction-Induction) teaching model, thereby changing the traditional teaching pattern of "spoon-feeding"; when it comes to the independent learning mode, the self-adaptive system can aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Torrano and González-Torres [184] reports on the initial validation study of motivational scales for secondary education students in Spain. Mei, Guo and Li [124] describes the design of a multimedia-based English pronunciation learning system with a self-adaptive learning mode. Laitinen, Piazza and Stenvall [99] presented the qualitative study that explores learning processes in smart city organizations in Helsinki and Catania.…”
Section: A Cluster Of Learning and Education Researchmentioning
confidence: 99%
“…Torrano and González-Torres [184] reports on the initial validation study of motivational scales for secondary education students in Spain. Mei, Guo and Li [124] describes the design of a multimedia-based English pronunciation learning system with a self-adaptive learning mode. Laitinen, Piazza and Stenvall [99] presented the qualitative study that explores learning processes in smart city organizations in Helsinki and Catania.…”
Section: A Cluster Of Learning and Education Researchmentioning
confidence: 99%
“…Most of these studies were focused on teaching English as a foreign language. For example; flipped learning (Kırmızı & Kömeç, 2019;Suranakkharin, 2017;Teng, 2017), computer assisted learning (Alhujaylan, 2019;Enayati & Gilakjani, 2020;Kızmaz, 2019) mobile learning (Almogheerah, 2020;Bensalem, 2018;Şahan, Çoban & Razı, 2016), multimedia (Kaymak, 2019;Mei, Guo & Li, 2017;Zhao et al, 2019), augmented reality (Akçayır & Akçayır, 2016;Ho, Hsieh, Sun & Chen, 2017;Tsai, 2020) and such studies were conducted on the role of teaching English as a foreign language. There are many studies on the role of technology integration in teaching English as a foreign language in the literature.…”
Section: The Importance Of Studymentioning
confidence: 99%
“…Literature [14] combines the characteristics of the English aesthetics course and constructs an Internet-based multimode teaching method for the English and American literature course to stimulate the students' listening and visualization, to enhance the interactive ability of the teaching classroom, and to help them get more exposure to the English and American literature and to improve their English literary literacy. An adaptive learning model based on a multimedia English pronunciation learning system that includes both teaching and independent learning modes was proposed in the literature [15]. After applying it to the teaching of "English Literature" fine courses, it is found that the learning mode has significant teaching practicability, which can significantly improve the teaching efficiency and students' independent learning ability.…”
Section: Introductionmentioning
confidence: 99%